Numerical simulation of rotating flow of CNT nanofluids with thermal radiation, ohmic heating, and autocatalytic chemical reactions - S. Eswaramoorthi; Saleem Nasir; K. Loganathan; M. Satyanarayana Gupta; Abdallah Berrouk (Alexandria Engineering Journal)
The dispersion of carbon nanotubes in conventional fluids provides a variety of applications, using their unique features to develop efficiency, performance, and functionality in many industrial and scientific processes. Some of the applications are energy conversion, fluid stirring, aligned nanocomposites, heat exchangers, electronics cooling, etc. Considering the aforementioned applications, this communication presents a comparative examination of the rotating flow of CNTs past a stretchable sheet with suction and velocity slip. This study is unique because it looks at the non-linear radiative, Darcy–Forchheimer, and rotational flow of CNTs past a stretchable sheet with considering ohmic heating and homogeneous/heterogeneous reactions. These type of issues have not been previously discussed. Suitable conversions are adopted to alter the governing nonlinear PDEs into nonlinear ODEs. The reduced ODEs are numerically reckoned by adopting the bvp4c scheme in MATLAB. The repercussions of flow factors on velocity, temperature, nanoparticle concentration, skin friction coefficients, and local Nusselt number are provided via tables and graphs. It is revealed that the primary velocity profile dwindles when augmenting the values of suction/injection, porosity, rotational, and magnetic field parameters. The temperature ratio and radiation parameters contribute to the thermal profile’s development. The magnetic field parameter and the Forchheimer number play a dual role in both directional skin friction coefficients. The larger values of radiation and temperature ratio parameters improve the heat transfer rate.